Constitutive Negative Regulation of R Proteins in Arabidopsis also via Autophagy Related Pathway? - Pečenková, Tamara; Sabol, Peter; Kulich, Ivan; Ortmannová, Jitka; Žárský, Viktor (Frontiers in Plant Science, 2016)
Even though resistance (R) genes are among the most studied components of the plant immunity, there remain still a lot of aspects to be explained about the regulation of their function. Many gain-of-function (GOF) mutants of R genes and loss-of-function (LOF) of their regulators often demonstrate up-regulated defence responses in combination with dwarf stature and/or spontaneous leaf lesions formation. For most of these mutants, phenotypes are a consequence of an ectopic activation of R genes. Based on the compilation and comparison of published results in this field, we have concluded that the constitutively activated defence phenotypes recurrently arise by disruption of tight, constitutive and multilevel negative control of some of R proteins that might involve also their targeting to the autophagy pathway. This mode of R protein regulation is supported also by protein-protein interactions listed in available databases, as well as in silico search for autophagy machinery interacting motifs. The suggested model could resolve some explanatory discrepancies found in the studies of the immunity responses of autophagy mutants.